The war and the reconformation of local power: Puno, 1879-1890 - Hünefeldt, Christine (1990)
We want to ask two questions. The first: What happened in Puno during the War of the Pacific?; the second: What were the consequences of this war from the perspective of a recomposition of power relations at the local level? Our first question is inserted in a debate that has lasted for at least a decade and that refers to the characteristics of the behavior of Peruvians in the context of a national war.